2007
DOI: 10.1089/aid.2007.0045
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Plasma and Breast Milk after Single-Dose Nevirapine in Subtype C HIV Type 1: Population and Clonal Sequence Analysis

Abstract: Single-dose nevirapine (SD NVP) reduces intrapartum HIV-1 transmission, but nonnucleoside reverse transcription (NNRTI) resistance mutations can emerge. Population sequencing among 32 subtype C HIV-1-infected, SD NVP-exposed Zimbawean women demonstrated NNRTI resistance in 25/32 (78%) women: 23/30 (77%) at 2 weeks, 11/31 (35%) at 8 weeks, and 5/27 (19%) at 24 weeks. A total of 447 unique TA clones (median = 28 per time point), from four women with resistance at 8 weeks but wild-type virus by population sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
3
23
1
Order By: Relevance
“…In the management of infants, utilising CNSpenetrating regimens are not always possible. Single-dose NVP (sd-NVP) is widely used in sub-Saharan Africa in the prophylactic treatment of infants in the management of PMTCT; however there is controversy over its use due to the emergence of NNRTI resistance mutations developing readily (Arrivé, et al, 2007;Kassaye, et al, 2007).…”
Section: Antiretroviral Eramentioning
confidence: 99%
“…In the management of infants, utilising CNSpenetrating regimens are not always possible. Single-dose NVP (sd-NVP) is widely used in sub-Saharan Africa in the prophylactic treatment of infants in the management of PMTCT; however there is controversy over its use due to the emergence of NNRTI resistance mutations developing readily (Arrivé, et al, 2007;Kassaye, et al, 2007).…”
Section: Antiretroviral Eramentioning
confidence: 99%
“…So far, only three studies have determined the emergence of NVP-resistant virus in breast milk following intake of NVP-SD. Two studies analysed breast milk of women infected with HIV-1 subtype C and showed that HIV-1 variants in breast milk emerged frequently and often differed in sequences from resistant HIV-1 variants in plasma [13,14]. Recently, a third study analysed breast milk samples of women mainly infected with HIV-1 subtypes A and D using a population-based approach with a detection limit for drug-resistant HIV-1 variants of approximately 20% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Participant plasma samples were collected from the Malaria and HIV-1 in Pregnancy (MHP) prospective cohort. [17][18][19][20] The MHP study was approved by the Malawi College of Medicine Research Committee and the Institutional Review Board at the University of North Carolina at Chapel Hill. Informed consent was obtained from all mothers.…”
mentioning
confidence: 99%
“…Informed consent was obtained from all mothers. Women and their newborn infants received single-dose nevirapine according to the HIV-NET 012 protocol 20 and breastfeeding was initiated. Plasma and cell pellets were isolated from blood collected from the mothers at labor-ward admission, and blood was collected via heel-sticks from the infants at three time points: within 48 h of birth, at 6 weeks, and at 12 weeks of age.…”
mentioning
confidence: 99%